2015
DOI: 10.3389/fnsys.2015.00139
|View full text |Cite
|
Sign up to set email alerts
|

The state of sleep and the current brain paradigm

Abstract: Up to the present time cerebral cortex was considered as substrate for realization of the highest psychical functions including consciousness. Cortical sensory areas were regarded as structures specialized for processing of information coming from one particular modality (visual, auditory, somatosensory, and so on). However, studies of cortical activity in sleep-wake cycle demonstrated that during sleep the same neurons in the same cortical areas switch to processing of signals coming from the various visceral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
3
6
0
2
Order By: Relevance
“…We can assume that the information flow from the heart to the brain might be shown in GC h→b analysis since the thalamus also communicates the visceral information to the insula and medial prefrontal areas [64]. These results are in agreement with those of previous studies about visceral responses in cortical sensory areas during sleep [6570]. In these studies, it was revealed that some cortical areas responded to visceral activities including heart activity during sleep, suggesting that visceral projections to some cortical areas are activated only during sleep [6570].…”
Section: Discussionsupporting
confidence: 88%
“…We can assume that the information flow from the heart to the brain might be shown in GC h→b analysis since the thalamus also communicates the visceral information to the insula and medial prefrontal areas [64]. These results are in agreement with those of previous studies about visceral responses in cortical sensory areas during sleep [6570]. In these studies, it was revealed that some cortical areas responded to visceral activities including heart activity during sleep, suggesting that visceral projections to some cortical areas are activated only during sleep [6570].…”
Section: Discussionsupporting
confidence: 88%
“…The prescient experiments of Libet (1985) have shown that volition show close correlation to the brain's background electrical fluctuations. However, cortical areas are universal processors tuned not so much for particular sensory modality, but rather for particular algorithms of incoming information processing (Pigarev and Pigareva 2015). During stimuli-evoked activity or cognitive demands, the brain transitorily exhibits functional conformations-other than the spontaneous ones-,which are linked with specific psychological correlates (Cole et al 2014).…”
Section: Brainwaves: Stimulus Builds On the Dmnmentioning
confidence: 99%
“…The visceral theory of sleep, developed by I. N. Pigarev [15,16,17,18] Although at first sight this hypothesis seems paradoxical, it is in harmony with findings of computational science that the universal processors are much more effective way to build a computer than development of processors specialized for a single function.…”
Section: The Visceral Theory Of Sleepmentioning
confidence: 95%